Succinic acid fermentation with immobilized Actinobacillus succinogenes using hydrolysate of carbohydrate-rich microalgal biomass. (December 2021) - Chiang, Ya-Yun; Nagarajan, Dillirani; Lo, Yung-Chung; Chen, Chun-Yen; Ng, I-Son; Chang, Chien-Hsiang; Lee, Duu-Jong; Chang, Jo-Shu
Graphical abstract: Highlights: Immobilization of A. succinogenes in PVA improved SA titer by 1.35 fold. SA yield of 0.582 g g −1 glucose was obtained in batch mode with 40 g L -1 glucose. Fed-batch fermentation integrated with SA removal improved SA titer to 59.5 g L -1. Batch fermentation with sugar-rich algal biomass attained an SA yield of 0.72 g g −1. Microalgal hydrolysate successfully replaced yeast extract in a fermentation medium. Abstract: This work aimed to study the efficiency of polyvinyl-alcohol-immobilized Actinobacillus succinogenes ATCC55618 for succinic acid (SA) production. Batch fermentation (pH 7, 45% CO2 gas at 0.04 vvm ) using glucose (40 g L -1 ) resulted in SA titer, 26.7 g L -1 ; productivity, 3.33 g L -1 h −1 ; yield, 0.621 g g − 1. Fed-batch mode with cyclic extrication of SA from the medium markedly enhanced the yield to 0.699 g g −1 and concentration to 59.5 g L -1 . Batch fermentation using sugars derived from Chlorella vulgaris ESP-31 without yeast extract gave a SA productivity, concentration, and yield of 1.82 g L -1 h −1, 36.1 g L -1, and 0.720 g g − 1, respectively. Furthermore, continuous fermentation (at 6 h HRT) with microalgal sugar improved the productivity and yield to 3.53 g L -1 h −1 and 0.62 g g −1, respectively, which is comparable to those obtained by using glucose. This study reports the highest productivity for SA fermentation using microalgae-derived sugars.